Enhancing Customer Retention in B2B Digital Marketing Agency in Indonesia (Case Study of BIZGO Digital) - Farah Andayani (Journal of International Conference Proceedings, 2021)
The trend of digital marketing is growing in Indonesia. It is also supported by the pandemic season where offline selling is not available as much as before. People start to shift into offline platforms. Unfortunately, with the characteristics of emerging markets where acceptability, accessibility, as well as affordability is still low, study reveals that three-quarters of Indonesiaâ€™s SMEs are missing out on most of the benefits of digital technologies. Looking at these opportunities, BIZGO Digital offers digital marketing services which target the business owners and MSMEs to establish their online presence. Due to its replicable services, BIZGO is able to maintain this competitive advantage. As the agency grows, BIZGO is able to take more orders from clients as the systems are already well established. Previously, BIZGO portrayed an advertising strategy which led to failure in promoting a B2B agency.Â  Bizgo realizes the need to implement customer relationship management to increase customer retention rate and cross selling strategy. How can BIZGO, as the B2B Digital Marketing agency implement an effective strategy to increase customer retention rate?